Distribution, larval abundance, spawning and early development of saddle oyster Placuna ephippium (Philipsson, 1788) from Merambong Shoal - Wong, Nur Leena Wai Sin (2013)
Placuna ephippium (Placunidae) has not been previously studied in Malaysia although it has been known to the local coastal communities in Pulai River Estuary,Johor as Senteng and has been collected for food for generations. Placuna ephippium has sweet and succulent meat and adductor muscle. It is a delicacy among local shore communities. This species was selected in this study as it has high potential as new aquaculture product with its great taste and durability in high impact area. The distribution of this species and other epifaunal bivalve in Merambong Shoal seagrass bed has been studied, along with the diversity and coverage of marine macrophytes,the sediment texture profile of Merambong Shoal, and their correlations with bivalve distribution. Merambong Shoal seagrass bed sediments are loamy sand and sandy in texture. The abundance in density and distribution of 15 epifaunal bivalve species from 10 families have been estimated, and the coverage of 7 seagrass species and 1 genus of macroalgae on the shoal during low tide were calculated. Placuna ephippium has highest abundance in the southernmost shoal and none was found at the northern most station. Anadara gubernaculum was found dominant on the seagrass shoal and specimens found mostly on the more sheltered northern shoal. Modiolus philippinarum distributed only in southern shoal facing the incoming wave. Epifaunal bivalve abundance and macrophyte coverage were more heterogeneous in the southern shoal while more homogenous at the northern shoal. Spearman’s rank correlation coefficient tested between epifaunal bivalve abundance and macrophyte coverage shows weak and non-significant results. Negative correlation was observed between the abundance of Circe scripta and Ulva spp. coverage (P < 0.05). Temporal larval abundance of Placunidae and other bivalves were explored aiming to discover the natural spat fall season and explore the theory of seagrass meadow being a nursery for non-habitant bivalve larvae. The correlations between temporal bivalve larval abundance, environmental parameters and rainfall were investigated. Placunidae larvae were found from September 2007 to January 2008 but none was found in February 2008. The highest abundance of Placunidae was recorded in November 2007 with density 226 larvae m-3. Major peak on total bivalve larval abundance was noticed between November 2007 and January 2008, while a low peak was observed in June 2007. Larvae of six bivalve families were identified by umbonal shell morphology with Mytilidae larvae highest in abundance during November 2007 (7345 larvae m-3). No significant correlation was found between bivalve larvae abundance and seawater parameters like temperature, salinity, DO, pH and TSS. There are significant correlations between total larvae abundance and total rainfall within a week and two weeks prior to sample collection (P < 0.01). Early development of P. ephippium was recorded and described. Placuna ephippium broodstocks were collected during low tide in Merambong Shoal seagrass bed. Thermal cycling procedure had successfully induced the spawning of this species. The average size of the spherical eggs before fertilisation was 57.65 ± 5.97 μm in diameter and 90.91 ± 2.04% eggs were fertilised successfully. Embryos developed into straight-hinged larvae 22 hours after fertilisation. Umbo started to take shape from Day-2. Larval shells are inequivalve with right valve almost flat and left valve inflated. Larvae developed into pediveliger on Day-9 and started to form plantigrade on Day-11. Rapid decreases were observed in survival rate during settlement.